The Politics of Cultural Differences : Social Change and Voter Mobilization Strategies in the Post-New Deal Period - Leege, David C. (Book collections on Project MUSE., 2002)
How did Republicans manage to hold the White House through much of the past half century even as the Democratic Party held the hearts of most American voters? The authors of this groundbreaking study argue that they did so by doing what Democrats have also excelled at: triggering psychological mechanisms that deepen cultural divisions in the other party's coalition, thereby leading many of its voters either to choose the opposing ticket or to stay home.